2021
DOI: 10.1155/2021/8204522
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Continuous Nursing Intervention on Aplastic Anemia Patients Based on the “Information-Motivation-Behavioral Skills Model”

Abstract: Objective. To explore the effect of continuous nursing care based on the “information-motivation-behavioral skills model” (IMB) in the intervention of patients with aplastic anemia. Methods. A total of 90 patients with aplastic anemia who were admitted to our hospital from June 2019 to January 2021 were included in the study. The patients were divided into an observation group and a control group according to the random number table, with 45 patients in each group. The control group received routine nursing ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Similar to the IMB-model, using online education showed positive effects on health knowledge, motivation, and perceived objective skills, 19 enhanced self-care ability, and improved quality of life. 20 This is similar to other studies on health-promoting behaviors which significantly predicted higher quality of life for all participants. 21 Thus, this media can help the participants to increase physical activity and healthy eating behavior, and to decrease their sedentary behavior resulting in weight loss.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the IMB-model, using online education showed positive effects on health knowledge, motivation, and perceived objective skills, 19 enhanced self-care ability, and improved quality of life. 20 This is similar to other studies on health-promoting behaviors which significantly predicted higher quality of life for all participants. 21 Thus, this media can help the participants to increase physical activity and healthy eating behavior, and to decrease their sedentary behavior resulting in weight loss.…”
Section: Discussionsupporting
confidence: 90%
“…16,17 The results of this study showed that the nursing satisfaction of patients undergoing Mode-II intervention was higher than that of the patients undergoing the Mode-I intervention. Shen W et al 19 showed that information motivation behavioral skills model (IMB) significantly improved nursing satisfaction, medication compliance, self-care ability and quality of life of patients with aplastic anemia, which is consistent with the results of our study.…”
Section: Our Study Demonstrated That Intervention Of Information Moti...supporting
confidence: 92%
“…The miR-155 and NLRP3 levels were calculated by 2-△△Ct method. ⑧ The quality of life before and after treatment was evaluated by the comprehensive quality of life assessment questionnaire-74 (GQOLI-74) [ 11 ], which included four dimensions, four factors in each dimension, and a total of 16 factors (64 items). The highest score of each factor was 20 points, and the highest score of each dimension was 80 points.…”
Section: Methodsmentioning
confidence: 99%